2023
DOI: 10.1038/s41420-023-01511-0
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ elicits the ocular surface pathology mimicking dry eye through direct modulation of resident corneal cells

Abstract: Despite accumulating evidence indicating a key role of interferon-γ (IFN-γ)-producing immune cells in ocular infection and immunity, little is known about the direct effects of IFN-γ on resident corneal cells or on the ocular surface. Here, we report that IFN-γ impacts corneal stromal fibroblasts and epithelial cells to promote inflammation, opacification, and barrier disruption on the ocular surface, leading to dry eye. Our results demonstrated that IFN-γ dose-dependently induced cytotoxicity, pro-inflammator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…IFN-γ and IL-17 are pathogenic to the corneal epithelium (19,27,29), and conjunctival NK cells and other innate immune cells represent a significant source of these cytokines in the ocular surface (30,(34)(35)(36)(37). Using a non-surgical DED model, Coursey et al (35) showed that conjunctival IFN-γ and Th1-associated chemokines in Rag1KO mice increase after 5 days of desiccating stress but return to baseline levels by day 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IFN-γ and IL-17 are pathogenic to the corneal epithelium (19,27,29), and conjunctival NK cells and other innate immune cells represent a significant source of these cytokines in the ocular surface (30,(34)(35)(36)(37). Using a non-surgical DED model, Coursey et al (35) showed that conjunctival IFN-γ and Th1-associated chemokines in Rag1KO mice increase after 5 days of desiccating stress but return to baseline levels by day 10.…”
Section: Discussionmentioning
confidence: 99%
“…Effector CD4 + T cells in DED are mostly Th1 and Th17 (14,15), which promote type 1 and type 3 immunity, respectively (23), by releasing proinflammatory cytokines and recruiting other immune cells (23,24). IFN-γ, a hallmark type 1 cytokine, exerts a deleterious effect on the ocular surface by promoting both the apoptosis of conjunctival goblet cells and corneal epithelial cells and the squamous metaplasia of corneal epithelial cells (12,(25)(26)(27)(28)(29). IL-17, a hallmark type 3 cytokine, induces corneal epithelial cells to secrete matrix metalloproteinases, which degrade intercellular junctions and lead to corneal barrier disruption (19,30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other thought is that the blocking of IL-4 pathways may be driving more of a type 1 response on the eye [ 21 ]. That type 1 response is driven by cytokines, such as interferon-gamma, and those are definitely known to drive ocular surface scarring, [activation] of cytotoxic T cells, and accumulation of cytotoxic T cells on the ocular surface [ 22 , 23 ], which can [cause] the signs of inflammation and drive advanced ocular surface changes, such as scarring and neovascularization of the cornea [ 24 ].…”
Section: What Are Osd and Why Do They Matter For Dermatology Providers?mentioning
confidence: 99%